Relationship between investment and dividend decisions: researches of developed and emerging equity markets - Гульназ Байрасовна Шагалеева (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2013)
Gulnaz Bayraovna ShagaleyevaThe paper contains a survey of empirical studies on the relationship of investment and dividend decisions of the company. Reviewed scientific works are organized by testable hypotheses and studied samples (developed and developing capital markets).